The Expression Profiles and Clinical Significance of Mixed Lineage Kinases in Glioma - Jin Huang; Yuankun Liu; Gaosong Wang; Yuning Chen; Yifan Shen; Jiahao Zhang; Wei Ji; Junfei Shao (Mediators of Inflammation)
Mixed lineage kinases (MLKs), comprising seven members: MLK1-4, dual leucine zipper kinase (DLK), leucine zipper kinase (LZK), and sterile alpha motif and leucine zipper containing kinase (ZAK), belong to the mitogen-activated protein kinase kinase kinase (MAP3K) family. These kinases are implicated in the progression of numerous cancers by activating mitogen-activated protein kinase (MAPK) cascades or functioning as ser/thr and tyr kinases. However, their specific roles in glioma remain elusive. In the present study, we utilized bioinformatics approaches to investigate the expression patterns of MLKs in low-grade gliomas (LGG) and glioblastoma multiforme (GBM). Additionally, we analyzed their clinical significance and delved into the potential mechanisms underlying MLK activity as well as their association with tumor-immune infiltrating cells (TIICs) in glioma. Furthermore, we conducted in vitro studies to elucidate the functional roles of MLK1-2 in glioma. Our findings revealed that the expressions of MLK1-2 were conspicuously downregulated in GBM and positively correlated with patients’ overall survival. Conversely, ZAK exhibited an opposing trend. Notably, our newly devised risk score model exhibited superior performance in predicting patient prognoses. Moreover, we analyzed the potential mechanisms of MLK activity and its interplay with tumor immune infiltration. Last, we validated the antitumor effect of MLK1-2 at the in vitro level. In summary, our study sheds new insights into the roles of MLKs in glioma, particularly MLK1-2, and their potential as therapeutic targets.